PROSES PELAKSANAAN DAN PERAWATAN KAPAL MENGGUNAKAN METODE SANDBLASTING PADA GALANGAN KAPAL PT BATAM MARINA SHIPYARD - Suryaningsih, Encis Indah; NG, Elvern Andrisen (JURNAL SAINS DAN TEKNOLOGI MARITIM, 2024)
Very corrosive and damaging sea conditions cause the hulls of sailing ships to easily corrode or become damaged, especially the lower hulls of ships which are in direct contact with sea water on a continuous basis. Therefore, maintenance and painting must be carried out to avoid work accidents on ships because it is possible that rusting can cause the ship's hull plates to become brittle. To minimize the occurrence of these things, it is necessary to carry out routine maintenance. One method used to maintain/improve the condition of the ship, especially the parts of the ship's hull that are affected by corrosion, is to use the sandblasting method to create a profile on the metal surface of the ship's hull or other parts. Sanblasting is also the first step in carrying out ship maintenance so that when painting or coating the paint it can stick better and make the repair results more optimal and of better quality.